Deciphering the role of host-gut microbiota crosstalk via diverse sources of extracellular vesicles in colorectal cancer - Yun Song; Min Shi; Yugang Wang (BMC, 2024)
Abstract Colorectal cancer is the most common type of cancer in the digestive system and poses a major threat to human health. The gut microbiota has been found to be a key factor influencing the development of colorectal cancer. Extracellular vesicles are important mediators of intercellular communication. Not only do they regulate life activities within the same individual, but they have also been found in recent years to be important mediators of communication between different species, such as the gut microbiota and the host. Their preventive, diagnostic, and therapeutic value in colorectal cancer is being explored. The aim of this review is to provide insights into the complex interactions between host and gut microbiota, particularly those mediated through extracellular vesicles, and how these interactions affect colorectal cancer development. In addition, the potential of extracellular vesicles from various body fluids as biomarkers was evaluated. Finally, we discuss the potential, challenges, and future research directions of extracellular vesicles in their application to colorectal cancer. Overall, extracellular vesicles have great potential for application in medical processes related to colorectal cancer, but their isolation and characterization techniques, intercellular communication mechanisms, and the effectiveness of their clinical application require further research and exploration.